PENGARUH ASIMETRI INFORMASI, UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL, DAN CAPITAL ADEQUACY RATIO TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2011 – 2013) - Ayu Susanti; R. Adri Satriawan Surya; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine the effect of information asymmetry, company size, ownership managerial and capital adequacy ratio on earning management. The population of this study is Banking Firm listed in Indonesia Stock Exchange in the period of 2011 – 2013. Based on purposive sampling method, there are 14 Banking firms as sample of this study. Test statistic used is multiple linear regression test and data obtained were processed using SPSS statistical software. The results of this research found that information asymmetry, company size, and capital adequacy ratio have a significant effect on earning management. While ownership managerial has no significant effect on earning management. Coeficient of determination (R2) valued 0.365 means that earning management is influenced by information asymmetry, company size, ownership managerial and capital adequacy ratio amounted 36.5%.Keywords: Earning Management, Information Assymetry, Company Size, Ownership Managerial, and Capital Adequacy Ratio